Association Between Serum Uric Acid Level & Severity of Coronary Artery Disease Using GENSINI Score in Patients Undergoing Coronary Angiography (Academia Journal of Medicine, 2022)
To assess the association of serum uric acid level and angiographic severity of coronary artery disease using GENSINI SCORE  in patients undergoing coronary angiography. Subjects and Methods: All Patients presenting with symptoms related to CAD (Coronary  Artery Disease) undergoing coronary angiography were included for the study. The GENSINI SCORE was used to evaluate the severity of  atherosclerotic lesions on angiogram. Results: Out of 140 subjects; 41.43% and 58.57% of the subjects were having normal Uric acid and  hyperuricemia which included 59.82% and 53.57% of the male and female respectively. Mean age among the subjects with normal Uric acid  and hyperuricemia was 56.51±8.07 and 58.47±9.16 years respectively Hypertension and diabetes mellitus was found more among subjects  with Hyperuricemia. Mean BMI (kg/m2) among the subjects with normal uric acid and hyperuricemia was 27.59±3.81 and 28.01±4.08 respectively. LDL-C (mmol/l) was comparatively more among subjects with hyper-uricemia. Single, double and triple vessel disease was  revealed in 72, 47 and 21 subjects respectively. Hyperuricemia was reported among 37.5%, 76.60% and 90.48% of the subjects in single,  double and triple vessel disease respectively. Out of 140 subjects; 1-14, 15-32 and >33 Gensini score was reported among 34.29%, 65% and  0.71% of the subjects respectively. Conclusion: There is a substantial link between serum uric acid levels and the existence and severity of  CAD, as well as the Gensini score. High SUA levels are linked to a higher risk of cardiovascular disease.
Keywords: Uric Acid Level; Severity of Coronary Artery Disease